Growth of the airway smooth muscle layer from late gestation to childhood is mediated initially by hypertrophy and subsequently hyperplasia. Issue 7 (9th March 2022) - Wang, Kimberley C. W.; Donovan, Graham M.; Saglani, Sejal; Mauad, Thais; James, Alan L.; Elliot, John G.; Noble, Peter B.
Abstract: Background and objective: The airway smooth muscle (ASM) layer thickens during development. Identifying the mechanism(s) for normal structural maturation of the ASM reveals pathways susceptible to disease processes. This study characterized thickening of the ASM layer from foetal life to childhood and elucidated the underlying mechanism in terms of hypertrophy, hyperplasia and extracellular matrix (ECM) deposition. Methods: Airways from post‐mortem cases were examined from seven different age groups: 22–24 weeks gestation, 25–31 weeks gestation, term (37–41 weeks gestation), <0.5 year, 0.5–1 year, 2–5 years and 6–10 years. The ASM layer area (thickness), the number and size of ASM cells and the volume fraction of ECM were assessed by planimetry and stereology. Results: From late gestation to the first year of life, normalized ASM thickness more than doubled as a result of ASM hypertrophy. Thereafter, until childhood, the ASM layer grew in proportion to airway size, which was mediated by ASM hyperplasia. Hypertrophy and hyperplasia of ASM were accompanied by a proportional change in ECM such that the broad composition of the ASM layer was constant across age groups. Conclusion: These data suggest that the mechanisms of ASM growth from late gestation to childhood are temporally decoupled, with early hypertrophy and subsequent proliferation. We speculate that the developing airway is highly susceptible to ASM thickening in the first year of life and that the timing of an adverse event will determine structural phenotype. Abstract : A period of rapid hypertrophic airway smooth muscle growth occurs in the first year of life, representing a critical window for disruption by disease processes and/or opportunity for clinical intervention. See related Editorial